An Active Lifestyle is Associated with Better Neurocognitive Functioning in Adults Living with HIV-infection - Fazeli, Pariya L. (2014)
Studies of healthy adults show that engagement in physical, social, and mental activities is associated with better cognitive outcomes, suggesting these activities may increase cognitive reserve. Given the prevalence and real-world impact of HIV-associated neurocognitive disorders (HAND), the present study examined the association between neurocognitive outcomes and self-reported proxies for physical exercise, social activity, and mental activity (employment was used as a proxy for mental activity) among 139 HIV-infected adults (M(age) = 48.7; 48% age 50+). Participants completed a neuromedical and neuropsychological battery and were classified based on the number of self-reported active lifestyle factors (ALFs; 0 to 3), including physical exercise, social activity, and current employment. The association between ALFs and both demographically-adjusted average neuropsychological T-scores and HAND diagnoses were examined. Results revealed that an increased number of ALFs was associated with better global neurocognitive performance as well as a lower prevalence of HAND. These cross-sectional findings suggest that an active engagement in life may bolster neurocognitive functioning, perhaps by enhancing cognitive and/or brain reserve. However, an alternative explanation might be that persons with better neurocognitive functioning are more inclined and able to engage in these life activities. Future studies should utilize neuroimaging methodology, longitudinal data, and interventional approaches to establish cause-effect relationships and uncover the neural mechanisms whereby physical, social, and mental stimulation may protect neurocognition via cognitive reserve among those living with HIV.